M train [compact disc, unabridged] - Smith, Patti (Books on Tape ; Random House Audio, 2015)
M Train begins in the tiny Greenwich Village cafe where Smith goes every morning for black coffee, ruminates on the world as it is and the world as it was, and writes in her notebook. Through prose that shifts fluidly between dreams and reality, past and present, and across a landscape of creative aspirations and inspirations, we travel to Frida Kahlo's Casa Azul in Mexico; to a meeting of an Arctic explorer's society in Berlin; to a ramshackle seaside bungalow in New York's Far Rockaway that Smith acquires just before Hurricane Sandy hits; and to the graves of Genet, Plath, Rimbaud, and Mishima.